THE INFLUENCE OF WORKLOAD AND COMPETENCY ON ORGANIZATIONAL PERFORMANCE WITH ORGANIZATIONAL CULTURE MEDIATION - Sitorus, Sunday Ade; Suwitho, Suwitho; Haditomo, Alfabetian Harjuno Condro; Nurfaidah, Resti; Ramlawati, Ramlawati; Hendarto, Totok; Hermawati, Adya; SUNDAY ADE SITORUS (Universitas Brawijaya, Indonesia, 2022)
The objective of this research is to analyze the effect of Workload on Organizational Culture, Competence on Organizational Culture, Workload on Organizational Performance, Competence on Organizational Performance, Organizational Culture on Organizational Performance, Workload on Organizational Performance mediated by Organizational Culture, and Competence on Organizational Performance with the mediation of Organizational Culture. The quantitative approach was used in which the survey was conducted with the questionnaire. Data were collected in the form of an ordinal Likert scale. The analytical model used in this research was Path Analysis. The research population included the employees of KPP Pratama Kriyorejo. Results showed that workload and competence had a significant effect on organizational performance, workload and competence did not significantly affect organizational culture, but workload and competence had a significant effect on organizational performance with the mediation of organizational culture.